Pemberdayaan Potensi Keagamaan Peserta Didik melalui Pentas PAI dengan Pendekatan Asset-Based Community Development (ABCD) di Desa Karangharja - Samsu Nurfalah; Deny Solihin; Siti Salma Septianata; Nisa Aprilia; Salma Rachmah; Mutiara Samrotul Aropah (Lembaga Pengembangan Kinerja Dosen, 2025)
Islamic Religious Education (PAI) plays a strategic role in shaping students’ character and developing their religious potential. However, religious learning often becomes less engaging if not presented creatively. The PAI Festival (Pentas PAI) in Karangharja Village, Pagelaran District, Cianjur Regency, was implemented to explore and foster students’ religious talents and interests through Islamic-themed competitions. This program applied the Asset-Based Community Development (ABCD) approach, focusing on mobilizing community religious assets such as Islamic teachers, preachers, and local religious institutions. The implementation consisted of five stages: discover, dream, design, define, and destiny. The results indicate that Pentas PAI effectively served as a medium for students to express their religious abilities, enhance enthusiasm for learning religion, and cultivate Islamic character values such as responsibility, sportsmanship, and confidence. Furthermore, the activity strengthened collaboration among schools, communities, and families in supporting religious education. By optimizing local assets and community participation, Pentas PAI successfully created an engaging and sustainable model of religious education at the village level.